Smart Tracking Device with Pulse Sensor via GSM/GPS Module - Delos Santos, Manuel Luis C.; Abaricia, Cecilia P.; Tinio, Ronaldo S.; Dorado, Aljohn L. (International Journal of Computing Sciences Research, 2024)
Purpose – This device was to detect the user’s location using a GSM/GPS module with a SIM card. It triggers when the user presses the push button twice and sends messages with the user’s location and pulse rate to the mobile phone. Method – Applied, quantitative, and descriptive types of research were the methods and designs used for the development of the working prototype. Likewise, closed-ended survey questionnaires for the 25 randomly selected respondents used the five-point rating scale that is based on ISO/IEC 9126 and ISO/IEC 27000, and hardware and software components, and analytical tools were integrated into the study. Results – The tabulated survey yielded a computed weighted mean of 4.43 with an overall verbal interpretation of “Agree” which means most of the respondents believed that the prototype was effective in terms of sending accurate information such as location and pulse BPM that helps a person with a medical condition or encountering an emergency such as being kidnapped by alerting their parents or guardians. Conclusion – In the final analysis, the study showed that the device has a user-friendly interface, is easy to use, and can operate efficiently based on the results of the survey conducted to determine its acceptability. Recommendations – The researchers recommend for those who wish to replicate this prototype that there is much more to develop and improve than the current prototype, which has difficulties in the following areas: maximizing battery power from 12 hours to 14 hours, minimizing the design of the prototype by using Arduino Nano, use vibration motor as an indicator. Likewise, the A9G GPRS/GSM+ GPS/BDS module should be used to minimize the dimensions of the prototype and include the emergency hotline or the number of police stations or barangay halls that can receive the message. Practical Implications – The device can track location effectively and provide heart rate measurements, making it a promising solution for personal tracking and health monitoring.